Comparison of maturity models - Khoshgoftar, Mohammad; Osman, Omar (2008)
Maturity models are one of the widespread areas in the field of improving organizational performance. Maturity models identify organizational strengths and weaknesses in addition to providing benchmarking information. Project management maturity models are important assessment tools for the profession. Companies assess their organizational performance and identify their weaknesses and strengths in terms of their needs and objectives and also characteristics of the models. The important issue here is that construction companies can assess their organizational performance by a comprehensive and useful model. This can help them compare their situation with other companies by using the same model. There are many maturity models like OPM3, P-CMM, CMMI, OPMMM, TMM, P3M3, SPICE, BPMM, FAAiCMM, (PM)2, Kerzner’s Project Management Maturity Model, Ibbs and Kwak Maturity Model, RMMM, TMM, etc. The aim of this study is to find out the best maturity model for using in construction companies. We will discuss four maturity models (OPM3, Prince, CMMI, and BPMM) and compare them in terms of variables such as: Publisher, Project Manager, Scope, Number of Maturity Levels, Date of Issue, Detail, Definition of Maturity, Culture, Referring to Standard, Discrete and Continues, Assessment difficulty, Assessment cost, Quantitative Results, Tangible of Result, Identifying weakness and Strong points, Continues Assessment, Training, Flexibility, Organization Strategic, Acceptability of Model, Simple and Understandable, Easy for Execution. The result will show that OPM3 is the best maturity model among four maturity model considered.